Джунгли или путешествие по тропическому лесу - Колпакова Ольга Валерьевна (Читаем сами, 2006)
Экземпляры: аб. (2007) / Инвентарный номер: 50788 / Цена: / Сис.шифр: 26.89(3) / Авт.знак: К 61 / ГРНТИ: 39.21 / ББК: 26.89(3)